Anti-ROR1 CAR-T cells: Architecture and performance - Osorio-Rodríguez, Daniel Andrés; Camacho, Bernardo Armando; Ramírez-Segura, César (Frontiers in Medicine, 2023)
The receptor tyrosine kinase-like orphan receptor 1 (ROR1) is a membrane receptor that plays a key role in development. It is highly expressed during the embryonic stage and relatively low in some normal adult tissues. Malignancies such as leukemia, lymphoma, and some solid tumors overexpress ROR1, making it a promising target for cancer treatment. Moreover, immunotherapy with autologous T-cells engineered to express a ROR1-specific chimeric antigen receptor (ROR1 CAR-T cells) has emerged as a personalized therapeutic option for patients with tumor recurrence after conventional treatments. However, tumor cell heterogeneity and tumor microenvironment (TME) hinder successful clinical outcomes. This review briefly describes the biological functions of ROR1 and its relevance as a tumor therapeutic target, as well as the architecture, activity, evaluation, and safety of some ROR1 CAR-T cells used in basic research and clinical trials. Finally, the feasibility of applying the ROR1 CAR-T cell strategy in combination with therapies targeting other tumor antigens or with inhibitors that prevent tumor antigenic escape is also discussed. Clinical trial registration https://clinicaltrials.gov/, identifier NCT02706392